Piloting an Interprofessional Narrative-Based Interactive Workshop for End-of-Life Conversations: Implications for Learning and Practice. (February 2023) - Canzona, Mollie Rose; Love, Deborah; Barrett, Rolland; Henley, Joanne; Bridges, Sara; Koontz, Adam; Nelson, Sharon
Background: Based on the principles of Narrative Medicine, this study explored a narrative-based workshop for multi-level interdisciplinary clinicians who have EOL conversations. Methods: Fifty-two clinicians participated in narrative-based interactive workshops. Participants engaged narrative in three forms: viewing narratives, writing/sharing narratives, and co-constructing narratives. Post workshop interviews were conducted and thematically analyzed. Results: Five themes characterized how the workshop shaped learning and subsequent care experiences: (1) learning to enter/respond to the patient stories, (2) communicating across professions and disciplines, (3) practicing self-care. Additional themes emphasized (4) barriers to narrative learning and (5) obstacles to applying narrative to practice. Discussion: Results highlight the function/utility of narrative forms such as the value of processing emotions via reflective writing, feeling vulnerable while sharing narratives, and appreciating colleagues' obstacles while observing patient-clinician simulations. Challenges associated with narrative such as writing anxiety and barriers to implementation such as time constraints are detailed to inform future initiatives.